3D Geometry / Hashimatun Saadah Mazlan - Mazlan, Hashimatun Saadah (2004)
This thesis project is about implementing 3D technology in teaching mathematics for the topic geometry. It is very useful for students in increasing their understanding of learning the topic because it is performed in a simple way for the user to understand. To develop this project, Swift 3D .V3 is used to develop the 3D model, Macromedia Director 8.5 as a platform, and Macromedia Flash Max for the content development. All these software were chosen because of their compatibility, performance and reliability. During the first phase, all 3D shapes and text are created. Then, the 3D objects will be exported to Macromedia Flash MX to create the combination of 2D animation and animations were also created using this software, The reason is to make the contents more interesting, attractive and effective. The movies created in Flash are compiled with Director and it will then finally publish the project to an executable file, on a compact disc.